Summary of Evaluation and Surgical Treatment of Hemorrhagic Stroke - Islamov Otaboy Akramugli; Juraev Anvar Mamatmurodugli; Ruzikulov Mahmud Majidovich (Research Parks Publishing LLC, 2021)
Stroke is one of the leading causes of death. Every 7th patient with stroke is of a hemorrhagic nature, from which the mortality rate is 35-40%, and disability is 75%, and 10% disabled are bedridden. The disease has social impact, as it is common among working-age population. In the past three decades, neurosurgeons conducted an active search for and introduction of new methods of treatment of primary intracerebral hematomas. That is, patients with extravasations have the most pronounced neurological deficit and require prompt action to eliminate it. Thus, the admission of patients to specialized neurosurgical department, the proper selection of patients for surgery, the use in surgery minimally invasive methods and usage of modern technologies postoperative mortality does not exceed 25%, and the time from diagnosis to the possibility of a complete rehabilitation therapy is 1.5-2 weeks